Pan masala habits and risk of oral precancer: A cross-sectional survey in 0.45 million people of North India - Divya Mehrotra; Sumit Kumar; Shambhavi Mishra; Sandeep Kumar; Prashant Mathur; C.M. Pandey; Arvind Pandey; Kishore Chaudhry (Journal of Oral Biology and Craniofacial Research)
Objectives: This cross-sectional community based study was conducted to estimate the prevalence of consumption habits for non tobacco pan masala (ASU) and the risk of developing oral precancer in North India. Methods: This study was conducted in the old town of Lucknow city in the state of Uttar Pradesh in India. Subjects residing for more than 6 months and aged 15 years or above, were enrolled in the study after their informed consent. A two page survey tool was used to collect the data. A three times more matched sample of non users was randomly obtained from this data to analyze and compare the final results. Results: 0.45 million subjects were surveyed. Majority of tobacco users were in the age group of 20–35 years among males and 35–39 years among females. Consumption of non tobacco pan masala among males as well as females was most common in 15–19 years of age group. Prevalence of oral precancer (leukoplakia, submucous fibrosis, erythroplakia, lichen planus, smokers palate and verrucous hyperplasia) was 3.17% in non tobacco pan masala users and 12.22% in tobacco users. The odds of developing oral precancer in non tobacco pan masala users was 20.71 (18.79–22.82) and in tobacco users was 88.07 (84.02–92.31) at 95% confidence interval against non users of both. Conclusion: The odds of developing oral precancer even with consumption of pan masala is high, even when it is consumed without tobacco. It is hence recommended to discourage this habit.